2014
DOI: 10.1530/joe-14-0425
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione-induced lipid droplet formation during osteogenic differentiation

Abstract: Chronic administration of the insulin-sensitising drugs, thiazolidinediones (TZDs), results in low bone mineral density and 'fatty bones'. This is thought to be due, at least in part, to aberrant differentiation of progenitor mesenchymal stem cells (MSCs) away from osteogenesis towards adipogenesis. This study directly compared the effects of rosiglitazone, pioglitazone, and netoglitazone treatment on osteogenesis and adipogenesis in MSCs derived from subcutaneous (SC) or visceral (PV) white adipose tissue. MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The resulting metabolic improvement is also contributed to by increased adiponectin secretion; the net result being improved insulin sensitivity and prevention/improvement of type 2 diabetes ( 106 ). Of course the weight gain has negative musculoskeletal and cosmetic implications and the enhanced adipocyte differentiation may be at the expense of reduced osteoblast differentiation in bone with consequent reduction of bone density ( 107 ).…”
Section: Implications For Pathophysiology/therapymentioning
confidence: 99%
“…The resulting metabolic improvement is also contributed to by increased adiponectin secretion; the net result being improved insulin sensitivity and prevention/improvement of type 2 diabetes ( 106 ). Of course the weight gain has negative musculoskeletal and cosmetic implications and the enhanced adipocyte differentiation may be at the expense of reduced osteoblast differentiation in bone with consequent reduction of bone density ( 107 ).…”
Section: Implications For Pathophysiology/therapymentioning
confidence: 99%
“…To determine whether any of these cells correspond to adipocyte progenitors, we exposed cultures to adipogenic conditions. Because activation of PPARγ (peroxisome-proliferator activated receptor gamma) by ligands such as thiazolidenediones can induce lipid accumulation in cells independently of adipogenic conversion 16 , we used a minimal adipogenic cocktail of 3-isobutyl-1-methylxanthine, dexamethasone and insulin (MDI). After approximately 6 days, we observed a loss of continuity between cells forming the capillary structure, and lipid droplets in cells within the capillaries ( Fig.…”
mentioning
confidence: 99%
“…Unlike most publications that used adipogenic cocktails containing multiple ingredients for the adipocyte differentiation from a range of progenitors in vitro, we found that rosiglitazone and insulin are necessary and sufficient for the adipogenic induction of CD34+CD31+ cells. While we are aware that rosiglitazone alone can induce a lipid accumulation in non-adipose cells 35 , the molecular signature for pan-adipocyte and brown/beige adipocyte markers, including a UCP-1 protein expression in select cells, confirms the mature adipocyte phenotype of some of the differentiated cells. Our two-ingredient adipogenic cocktail simplifies the procedural protocol and makes it more cost-effective.…”
mentioning
confidence: 77%